Efek intervensi hoki dalam ruangan pada kemampuan motorik dan kebugaran fisik pada remaja - Cahyono, Tedi; Hernawan, Hernawan; Vidya Hartono, Fajar; Nugraha, Hartman; Pasaribu, Ahmad Muchlisin Natas (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This study aimed to determine the intervention of hockey games in improving motor skills and physical fitness in adolescents. The research method used in this study was an experiment involving a control group. This research uses a pre-test-post-test randomized control group design, with a total sampling of 30 adolescents divided into 2 groups, namely the experimental group and the control group, each comprising 15 people. The determination of group division is divided randomly, and all subjects involved are used. Instruments used Children's Psychomotricity and Aptitude Scales (MSCA, USA). Physical fitness using physical fitness test instruments, which have been adjusted to the characteristics of the research subjects. The results showed that the intervention for 12 weeks in indoor hockey activity, intervention, and gross motor intervention showed a significance value of 0.034. Because the significance value < 0.05, Ho was rejected, compared to the results of participants in the study who were given an independent intervention program. The physical fitness data shows that the pre-test standard deviation is 1.30440 compared to the post-test 1.61211, this means that there is an increase in adolescent physical fitness. Thus, indoor hockey intervention has a significant influence on the physical fitness of adolescents. These findings prove that interventions in the form of physically engaging activities focusing on floor hockey sports may be a viable option for improving Motor Proficiency and Physical Fitness in Adolescents.